Porous silica particles and method for producing the same

JP2026168758APending Publication Date: 2026-10-16FUSO CHEM
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025062158
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-04
Publication Date
2026-10-16

Smart Images

  • Figure 2026168758000001
    Figure 2026168758000001
  • Figure 2026168758000002
    Figure 2026168758000002
  • Figure 2026168758000003
    Figure 2026168758000003
Patent Text Reader

Abstract

To provide porous silica particles with high mechanical strength. [Solution] A silica porous silica particle characterized by being obtained by performing a first heat treatment step in which a mixture of raw material porous silica particles obtained by the sol-gel method and a pyrolytic carbon source is heated at 1000 to 1200°C under an inert gas atmosphere to obtain a first heat-treated product, and a second heat treatment step in which the first heat-treated product is heated at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C under an oxygen-containing gas atmosphere to obtain a second heat-treated product.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to porous silica particles and a method for producing the same. [Background technology]

[0002] In applications such as pharmaceuticals, agrochemicals, cosmetics, detergents, or fabric softeners, porous particles or porous hollow particles are known to be used as sustained-release carriers for functional compounds such as drugs or fragrances.

[0003] Materials with a porous structure include porous silica particles, activated carbon, diatomaceous earth, silica gel, zeolite, pumice, charcoal, and seashells. Of these, porous silica particles, which have a controlled particle shape and excellent color and chemical stability, have traditionally been used as a sustained-release carrier for functional compounds in the above-mentioned pharmaceuticals, agricultural chemicals, cosmetics, detergents, or fabric softeners because they interfere less with other chemical components.

[0004] For example, Patent Document 1 discloses a hollow silica particle having an outer shell made of a silica layer, an average particle diameter of 10 nm or more and 1000 nm or less, and having a through hole in the outer shell whose opening shape is selected from circular, elliptical, and polygonal shapes.

[0005] Patent Document 2 describes a silicate ester composition containing a silicate ester having an alkoxy group obtained by removing a hydrogen atom from the hydroxyl group of a fragrance alcohol, with a specific surface area of ​​1 to 1000 m². 2 A fragrance is disclosed that contains a fragrance agent supported on porous particles having a concentration of / g and an average pore size of 0.4 to 100 nm.

[0006] Furthermore, Patent Document 3 discloses a spherical hollow silica particle composition, encapsulating agent, dispersion, and aqueous dispersion, which includes a group of spherical hollow silica particles having a shell layer, wherein the shell layer has one opening that connects the external space and the internal space, and when measuring the particle diameter of 100 or more spherical silica particles having a diameter of 1 / 10 or more of the diameter of the largest spherical silica particle per field of view with a scanning electron microscope, the particle diameter is 10 nm to 10 μm, and the number of spherical hollow silica particles having one opening on the surface with a diameter of 1 nm or more and 1 / 3 or less of the particle diameter of the spherical silica particle is 5% or more of the total number of spherical hollow silica particles measured. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2012-051770 [Patent Document 2] Japanese Patent Publication No. 2015-116334 [Patent Document 3] Japanese Patent Publication No. 2022-34094 [Disclosure of the Invention] [Problems that the invention aims to solve]

[0008] However, porous silica particles have low mechanical strength, raising concerns that they may break during process handling, such as during resin mixing. Therefore, there is a need for porous silica particles with high mechanical strength.

[0009] Patent Document 1 states that the average thickness of the outer shell made of silica layers should be as thin as possible while the perforated hollow silica particles can maintain their strength as a carrier, but it does not make any specific mention of the mechanical strength required in processes such as resin mixing.

[0010] Furthermore, although Patent Document 2 states that silica gel is suitable as a porous material, it contains sodium as an impurity, which presents a problem in that it cannot be used as a support for functional compounds that react with sodium among the sustained-release supports. Also, Patent Document 2 does not mention the mechanical strength required in processes such as resin kneading.

[0011] Furthermore, Patent Document 3 features hollow silica obtained by heating at 700°C to 900°C to obtain a dense shell, but Patent Document 3 also does not mention the mechanical strength required in processes such as resin mixing.

[0012] Therefore, an object of the present invention is to provide porous silica particles with high mechanical strength. In particular, an object of the present invention is to provide porous silica particles for sustained-release carriers with high mechanical strength. [Means for solving the problem]

[0013] In order to solve the above technical problems, the inventors conducted diligent research and found that by mixing porous silica particles produced by the sol-gel method with a pyrolytic carbon source, the resulting mixture was... (1) First, the porous silica particles are heated at 1000-1200°C in an inert gas atmosphere (first heat treatment). By heating the porous silica particles at high temperatures and carbonizing them through the thermal decomposition of a pyrolytic carbon source, carbon is generated between the porous silica particles, thereby suppressing sintering between the porous silica particles. At the same time, heating the silica portion at high temperatures improves the mechanical strength of the silica portion. (2) Next, the carbon is burned off by heating at a lower temperature than the heating temperature of the first heat treatment in an oxygen-containing gas atmosphere. We discovered that it is possible to obtain porous silica particles with high mechanical strength, which led to the completion of this invention.

[0014] That is, the present invention (1) provides porous silica particles characterized by being obtained by performing: a first heat treatment step of heating a mixture of raw material porous silica particles obtained by a sol-gel method and a thermally decomposable carbon source at 1000 to 1200°C in an inert gas atmosphere to obtain a first heat-treated product; and a second heat treatment step of heating the first heat-treated product at a temperature lower than the heating temperature of the first heat treatment step and in the range of 900 to 1000°C in an oxygen-containing gas atmosphere to obtain a second heat-treated product.

[0015] Further, the present invention (2) provides the porous silica particles according to (1), characterized in that the number proportion of particles broken by high-pressure homogenizer treatment at 245 MPa is 10% or less.

[0016] Further, the present invention (3) provides the porous silica particles according to (1), characterized in that the number proportion of particles broken when pressurized at an applied pressure of 190 MPa by a cold isostatic pressing method is 10% or less.

[0017] Further, the present invention (4) provides the porous silica particles according to (1), characterized in that the content of metal impurities is 100 mass ppm or less.

[0018] Further, the present invention (5) provides the porous silica particles according to (1), characterized in that the maximum frequency value of the pore size distribution is 0.1 to 20 nm.

[0019] Further, the present invention (6) provides the porous silica particles according to (1), characterized in that in the pore size distribution, the ratio of the total pore volume of 0 to 10 nm to the total pore volume of 0 to 100 nm is 1 to 10%.

[0020] Further, the present invention (7) comprises a first heat treatment step of heating a mixture of raw material porous silica particles obtained by a sol-gel method and a thermally decomposable carbon source at 1000 to 1200°C in an inert gas atmosphere to obtain a first heat-treated product, A second heat treatment step involves heating the first heat-treated product in an oxygen-containing gas atmosphere at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C to obtain a second heat-treated product. This invention provides a method for producing porous silica particles, characterized by having [a specific feature / feature]. [Effects of the Invention]

[0021] According to the present invention, porous silica particles with high mechanical strength can be provided. In particular, according to the present invention, porous silica particles for sustained-release carriers with high mechanical strength can be provided. [Modes for carrying out the invention]

[0022] The porous silica particles of the present invention are characterized by being obtained by performing a first heat treatment step in which a mixture of raw porous silica particles obtained by the sol-gel method and a pyrolytic carbon source is heated at 1000 to 1200°C under an inert gas atmosphere to obtain a first heat-treated product, and a second heat treatment step in which the first heat-treated product is heated at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C under an oxygen-containing gas atmosphere to obtain a second heat-treated product.

[0023] The porous silica particles of the present invention are either solid particles without internal cavities or hollow particles with internal cavities. When the porous silica particles of the present invention are solid particles, the silica forming the solid portion has a porous structure, and when the porous silica particles of the present invention are hollow particles, the silica forming the outer shell portion has a porous structure.

[0024] The porous structure, solid structure, and hollow structure of these silica particles originate from the structure of the raw porous silica particles.

[0025] The first heat treatment step for porous silica particles of the present invention is a step of heating a mixture of raw porous silica particles and a pyrolytic carbon source at 1000 to 1200°C under an inert gas atmosphere to obtain a first heat treatment product.

[0026] The porous silica particles used as raw materials in the first heat treatment step are porous silica particles obtained by the sol-gel method. Examples of porous silica particles include solid porous silica particles and hollow porous silica particles. In addition, core-shell particles, which have a core made of pyrolytic organic polymer particles and a shell made of porous silica, are also examples of porous silica particles.

[0027] The raw material porous silica particles are appropriately selected from porous silica particles produced by conventionally known sol-gel methods.

[0028] One method for producing solid, porous silica particles using the sol-gel method is to use one or more hydrolyzable silicon compounds (e.g., alkoxysilanes or derivatives thereof, such as tetraalkoxysilane or trialkoxysilane) as raw materials, perform hydrolysis and condensation reactions to obtain a silica particle dispersion, and then heat-dry the silica particle dispersion to obtain solid, porous silica particles.

[0029] The above hydrolyzable silicon compound is given by the following general formula (1): Si(OR 1 )4(1) (In formula (1), R 1 The group is an alkyl group having 1 to 8 carbon atoms. Examples include tetraalkoxysilanes or derivatives represented by [formula].

[0030] In a tetraalkoxysilane or derivative represented by general formula (1), R 1 This is an alkyl group, preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms, and may be the same or different. R 1 Specifically, these are methyl, ethyl, propyl, isobutyl, butyl, pentyl, and hexyl groups. R 1 Tetramethoxysilane (TMOS), which has a methyl group, R 1tetraethoxysilane (TEOS) in which the group is an ethyl group is preferable in that it produces silica satisfactorily. The derivative of tetraalkoxysilane is a product obtained by replacing a part of the molecular structure of tetraalkoxysilane with another atomic group. The tetraalkoxysilane or a derivative thereof may be used alone, or two or more thereof may be used in combination.

[0031] Examples of the tetraalkoxysilane represented by the general formula (1) include R 1 tetramethoxysilane in which the group is a methyl group, R 1 tetraethoxysilane in which the group is an ethyl group, or R 1 tetraisopropoxysilane in which the group is an isopropyl group is preferable. Further, examples of the derivative of tetraalkoxysilane represented by the general formula (1) include low condensates obtained by partially hydrolyzing the tetraalkoxysilane represented by the general formula (1). As the tetraalkoxysilane represented by the general formula (1) or a derivative thereof, tetramethoxysilane is preferable from the viewpoints of easy control of the hydrolysis rate, easy obtainment of fine silica particles, and little residual unreacted substances.

[0032] Further, examples of the hydrolyzable silicon compound include the following general formula (2): Si(OR 1 )3R 2 (2) (In formula (2), R 1 the group is an alkyl group having 1 to 8 carbon atoms, and R 2 the group is hydrogen or an alkyl group.) trialkoxysilane represented by the formula or a derivative thereof.

[0033] In the trialkoxysilane represented by the general formula (2) or a derivative thereof, R 1 is the same as R in the aforementioned general formula (1). 1 In the trialkoxysilane represented by the general formula (2) or a derivative thereof, R 2 ​This is hydrogen, or an alkyl group, preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. Derivatives of trialkoxysilanes are those in which some of the molecular structure of the trialkoxysilane is replaced by other atomic groups. Trialkoxysilane or its derivatives may be used alone or in combination of two or more.

[0034] Hydrolyzable silicon compounds such as tetraalkoxysilanes or their derivatives represented by general formula (1), or trialkoxysilanes or their derivatives represented by general formula (2), undergo hydrolysis and condensation in the reaction solvent to form a dispersion of silica particles.

[0035] Examples of dispersion solvents (reaction solvents) used when hydrolyzing and condensing hydrolyzable silicon compounds such as tetraalkoxysilanes or derivatives represented by general formula (1), or trialkoxysilanes or derivatives represented by general formula (2), include water or organic solvents containing water. The above organic solvents include one or more selected from hydrophilic organic solvents such as methanol, ethanol, isopropanol, n-butanol, t-butanol, pentanol, alcohols such as ethylene glycol, propylene glycol, and 1,4-butanediol, and ketones such as acetone and methyl ethyl ketone. Among these organic solvents, it is particularly preferable to use alcohols such as methanol, ethanol, and isopropanol, and from the viewpoint of post-treatment of the reaction solvent, the alkyl group (R) of the silicon compound of the raw material is preferred. 1 It is more preferable to use alcohols having the same alkyl group as the base (for example, methanol for tetramethoxysilane).

[0036] The amount of organic solvent used is not particularly limited, but it is preferable to use 5 moles or more and 50 moles or less per mole of hydrolyzable silicon compound such as tetraalkoxysilane or its derivatives represented by general formula (1), or trialkoxysilane or its derivatives represented by general formula (2). If the amount of organic solvent used is less than 5 moles per mole of hydrolyzable silicon compound, compatibility with the hydrolyzable silicon compound may be poor, and if it exceeds 50 moles per mole of hydrolyzable silicon compound, the manufacturing efficiency may decrease.

[0037] The amount of water added to hydrolyzable silicon compounds such as tetraalkoxysilane or its derivatives represented by general formula (1), or trialkoxysilane or its derivatives represented by general formula (2), is not particularly limited and should be an amount sufficient for the hydrolysis of the hydrolyzable silicon compound. Preferably, the amount of water added is about 2 to 200 moles per mole of hydrolyzable silicon compound such as tetraalkoxysilane or its derivatives represented by general formula (1), or trialkoxysilane or its derivatives represented by general formula (2). Furthermore, when adding an organic solvent containing water to a hydrolyzable silicon compound, the amount of water mixed into the organic solvent significantly affects the particle size of the resulting silica particles. By relatively increasing the amount of water added relative to the amount of organic solvent added, the particle size of the resulting silica particles can be made relatively larger, and by relatively decreasing the amount of water added relative to the amount of organic solvent added, the particle size of the resulting silica particles can be made relatively smaller. In this way, the particle size of the resulting silica particles can be arbitrarily adjusted by changing the mixing ratio of water and organic solvent.

[0038] For the hydrolysis and condensation reactions of hydrolyzable silicon compounds to obtain a silica particle dispersion, it is preferable to adjust the reaction solvent to be alkaline in the presence of a basic catalyst. Through the above adjustments, the reaction solvent is preferably controlled to a pH of 8.0 to 11.0, more preferably 8.5 to 10.5, allowing for the rapid formation of a dispersion of silica particles.

[0039] As for the basic catalyst mentioned above, from the viewpoint of preventing contamination with impurities, one or more selected from organic amines and ammonia are preferred, and one or more selected from ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide are particularly preferred.

[0040] To hydrolyze and condense silicon compounds in a reaction solvent, hydrolyzable silicon compounds such as tetraalkoxysilane or its derivatives represented by general formula (1), or trialkoxysilane or its derivatives represented by general formula (2), are added to a solvent containing water and stirred at a temperature of typically 0°C to 100°C, preferably 0°C to 50°C.

[0041] By stirring a silicon compound in a water-containing solvent, hydrolysis and dehydration condensation reactions proceed for hydrolyzable silicon compounds such as tetraalkoxysilane or its derivatives represented by general formula (1), or trialkoxysilane or its derivatives represented by general formula (2). First, the hydrolyzable silicon compounds such as tetraalkoxysilane or its derivatives represented by general formula (1), or trialkoxysilane or its derivatives represented by general formula (2), undergo dehydration condensation to form dimers. These dimers then undergo polymerization (oligomerization) to form spherical silica primary particles in the solvent, thereby obtaining silica particles in which silica primary particles are dispersed in the solvent. By hydrolyzing and condensing a silicon compound while stirring it in a water-containing solvent, silica particles with uniform particle size can be obtained.

[0042] Next, the silica particle dispersion obtained by the above hydrolysis and condensation reactions is heated and dried to obtain solid, porous silica particles.

[0043] Examples of methods for producing such solid porous silica particles include those described in Japanese Patent Publication No. 2005-060217 and Japanese Patent Publication No. 2025-15412.

[0044] Furthermore, a method for producing hollow porous silica particles as raw materials includes a core-shell particle formation step in which, in the presence of pyrolytic organic polymer particles, one or more hydrolyzable silicon compounds (e.g., alkoxysilanes or their derivatives) are used as raw materials, and hydrolysis and condensation reactions are carried out to form core-shell particles in which the pyrolytic organic polymer particles form the core and the hydrolyzed and condensed products of one or more hydrolyzable silicon compounds form the shell, thereby obtaining a core-shell particle dispersion; a solvent removal step in which the solvent is removed from the core-shell particle dispersion to obtain core-shell particles; and a calcination step in which the core-shell particles are calcined, or by pyrolysis and calcination, to obtain hollow porous silica particles as raw materials.

[0045] The organic polymer particles involved in the core-shell particle formation process are the core particles of the core-shell particles. The organic polymer particles are not particularly limited as long as they are thermally decomposed and burned away by firing or thermal decomposition and firing in the firing process. Examples of organic polymers for the organic polymer particles include homopolymers such as styrene and alkyl (meth)acrylate, and copolymers of these with other copolymerizable monomers.

[0046] An example of the preparation of organic polymer particles in the core-shell particle formation process is the following method for preparing organic polymer particles (1).

[0047] In the method for preparing organic polymer particles (1), an organic monomer polymerization reaction is carried out in a solution containing an organic monomer, a dispersant, a solvent, and a polymerization initiator to obtain organic polymer particles.

[0048] The organic monomers used in the method for preparing organic polymer particles (1) are not particularly limited as long as they can be used to produce organic polymer particles by polymerization. Preferred organic monomers are those that can form organic polymer particles that are easily burned away by thermal decomposition after forming a shell. Examples of organic monomers include styrene for producing polystyrene particles and methyl (meth)acrylate for producing poly(meth)acrylate (PMMA) particles (methyl (meth)acrylate is a general term for methyl methacrylate and methyl acrylate), with styrene being preferred. Furthermore, by copolymerizing styrene with alkyl (meth)acrylates or other copolymerizable monomers as organic monomers, polystyrene particles containing constituent units derived from hydrophobic monomers such as alkyl (meth)acrylates, or other copolymerizable monomer constituent units, can be obtained.

[0049] The dispersant in the method for preparing organic polymer particles (1) is not particularly limited as long as it can produce organic polymer particles. Examples of dispersants include polyvinylpyrrolidone (PVP), hydroxypropyl cellulose (HPC), polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene glycol (PPG), polypropylene oxide (PPO), collagen, and polysaccharides (gum arabic). When the organic polymer particles are polystyrene particles, the aggregation of polystyrene particles can be suppressed by using polyvinylpyrrolidone or hydroxypropyl cellulose as a dispersant, thereby suppressing the aggregation of core-shell particles obtained in the core-shell particle formation step. The dispersant may be used alone or in combination (mixture) of two or more types.

[0050] The solvent used in the method for preparing organic polymer particles (1) is water or a hydrophilic organic solvent. Examples of hydrophilic organic solvents include alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, and 1,4-butanediol; ketones such as acetone and methyl ethyl ketone; and esters such as ethyl acetate. Of the hydrophilic organic solvents, alcohols are preferred, and methanol, ethanol, and isopropanol are more preferred. The solvent may be a single solvent or a combination (mixture) of two or more solvents. Water or a mixed solvent of water and methanol is preferred as the solvent. By using a mixed solvent of water and methanol, organic polymer particles with a narrow particle size distribution can be obtained. When using a mixed solvent of water and methanol, the mass ratio of water to methanol (water:methanol) is preferably 5:95 to 50:50, more preferably 8:92 to 40:60, and more preferably 10:90 to 30:70.

[0051] The polymerization initiator in the method for preparing organic polymer particles (1) is not particularly limited as long as it can produce organic polymer particles. Examples of polymerization initiators include peroxides such as inorganic peroxides and organic peroxides, organic initiators such as azo compounds, and redox agents. Organic peroxides are represented by the general formula RO-OR, where R is an acyl group, alkyl group, ketone group, etc. Azo compounds are represented by the general formula A-CN=NC-A, where A is an amidine group, cyano group, carboxyl group, etc. Examples of polymerization initiators include benzoyl peroxide, 2,2'-azobis(isobutylamidine)dihydrochloride (AIBA), 4,4'-azobis-4-cyanovaleric acid, and azobisisobutyronitonyl (AIBN), preferably 2,2'-azobis(isobutylamidine)dihydrochloride (AIBA) and 4,4'-azobis-4-cyanovaleric acid, and more preferably 2,2'-azobis(isobutylamidine)dihydrochloride (AIBA). The polymerization initiator may be used alone or in combination (mixture) of two or more types.

[0052] In the method for preparing organic polymer particles (1), the concentration of the organic monomer in the solution is not particularly limited. The concentration of the organic monomer is preferably 0.1 to 20% by mass, and more preferably 0.2 to 11% by mass, relative to the solution.

[0053] In the method for preparing organic polymer particles (1), the amount of dispersant used is preferably 0.01 to 100% by mass, more preferably 0.05 to 100% by mass, relative to the organic monomer.

[0054] In the method for preparing organic polymer particles (1), the concentration of the dispersant in the solution is not particularly limited. The concentration of the dispersant is preferably 0.01 to 10% by mass, and more preferably 0.1 to 7% by mass, relative to the solution.

[0055] In the method for preparing organic polymer particles (1), the amount of polymerization initiator used is preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, relative to the organic monomer.

[0056] In the method for preparing organic polymer particles (1), the concentration of the polymerization initiator in the solution is not particularly limited. The concentration of the polymerization initiator is preferably 0.01 to 1% by mass relative to the solution.

[0057] In the method for preparing organic polymer particles (1), the polymerization reaction of the organic monomer is carried out in a solution containing an organic monomer, a dispersant, a solvent, and a polymerization initiator, preferably while the polymerization reaction is carried out while the solution is mixed and stirred.

[0058] The reaction temperature during the polymerization reaction in the method for preparing organic polymer particles (1) is not particularly limited, but is preferably 30°C or higher and below the boiling point of the solvent, and more preferably 40 to 90°C and below the boiling point of the solvent. By setting the reaction temperature of the polymerization reaction within the above range, the solvent does not evaporate, and the polymerization reaction can proceed smoothly. The reaction time of the polymerization reaction is not particularly limited, but is preferably 1 minute to 12 hours, and more preferably 10 minutes to 10 hours. By setting the reaction time of the polymerization reaction within the above range, the polymerization reaction can proceed smoothly.

[0059] The organic polymer particles obtained by the method for preparing organic polymer particles (1) are suitable as organic polymer particles to be used in the core-shell particle formation process.

[0060] The one or more hydrolyzable silicon compounds used in the core-shell particle formation process are the same as the one or more hydrolyzable silicon compounds used in a method for producing solid, porous silica particles.

[0061] The solvent used in the core-shell particle formation process is water or a hydrophilic organic solvent. Using water as the solvent allows for inexpensive and safe formation of core-shell particles. Preferred hydrophilic organic solvents include alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, and 1,4-butanediol; ketones such as acetone and methyl ethyl ketone; and esters such as ethyl acetate. More preferably, the hydrophilic organic solvent is an alcohol, and more preferably methanol, ethanol, or isopropanol. The solvent may be used alone or in combination (mixture) of two or more types. Examples of solvents include water, or a mixed solvent of water and a hydrophilic organic solvent (such as methanol), with a mixed solvent of water and a hydrophilic organic solvent (such as methanol) being preferred. The mass ratio of the hydrophilic organic solvent (such as methanol) to water in the mixed solvent is not particularly limited. When a mixed solvent of water and methanol is used, the mass ratio of the hydrophilic organic solvent to water is preferably 50:50 to 95:5, and more preferably 60:40 to 95:5.

[0062] The basic catalyst used in the core-shell particle formation process is not particularly limited. As the basic catalyst, organic basic catalysts that do not contain metal components and inorganic catalysts that do not contain metal components are preferred in that they can avoid the inclusion of metal impurities. Preferred organic base catalysts include nitrogen-containing organic base catalysts such as ethylenediamine, diethylenetriamine, triethylenetetraamine, urea, ethanolamine, tetramethylammonium hydroxide (TMAH), tetramethylguanidine, and basic amino acids. Aquatic ammonia is a preferred inorganic base catalyst. The basic catalyst may be used alone or in combination of two or more types.

[0063] In the core-shell particle formation process, one or more hydrolyzable silicon compounds (e.g., tetraalkoxysilane or its derivative, trialkoxysilane or its derivative) and a basic catalyst are added to organic polymer particles dispersed in a solvent.

[0064] At this time, the concentration of organic polymer particles in the dispersion of organic polymer particles is preferably 0.01 to 50% by mass, more preferably 0.01 to 20% by mass, relative to the dispersion of organic polymer particles. Furthermore, the amount of one or more hydrolyzable silicon compounds added is preferably 100 to 600% by mass, more preferably 100 to 500% by mass, relative to the organic polymer particles. Furthermore, the amount of basic catalyst added is preferably 0.1 to 100% by mass, more preferably 1 to 90% by mass, relative to one or more hydrolyzable silicon compounds. Furthermore, if two or more hydrolyzable silicon compounds are added, the above-mentioned amount of addition refers to the total amount of those compounds added.

[0065] In the core-shell particle formation step, one or more hydrolyzable silicon compounds and a basic catalyst are added to organic polymer particles dispersed in a solvent, and the mixture is stirred to carry out hydrolysis and condensation reactions of one or more hydrolyzable silicon compounds, generating hydrolyzed and condensed products of one or more hydrolyzable silicon compounds on the surface of the organic polymer particles, thereby coating the organic polymer particles with hydrolyzed and condensed products of one or more hydrolyzable silicon compounds and forming core-shell particles.

[0066] The reaction temperature in the core-shell particle formation step is not particularly limited, but is preferably 5 to 200°C, and more preferably 5 to 150°C. By setting the reaction temperature in the core-shell particle formation step within the above range, the solvent does not evaporate, and the reaction can proceed smoothly. Furthermore, the reaction time in the core-shell particle formation step is not particularly limited, but is preferably 1 to 1200 minutes, and more preferably 1 to 600 minutes. By setting the reaction time in the core-shell particle formation step within the above range, the shell coating reaction can be carried out smoothly.

[0067] The core-shell particle formation process can yield core-shell particles having a core made of organic polymer particles and a shell made of hydrolyzable silicon compounds and condensates that coat the organic polymer particles.

[0068] Then, in the presence of thermally decomposable organic polymer particles, more specifically in a dispersion of thermally decomposable organic polymer particles, hydrolysis and condensation reactions are carried out using one or more hydrolyzable silicon compounds (e.g., alkoxysilanes or their derivatives) as raw materials. This yields a core-shell particle dispersion, which is a dispersion of core-shell particles in which the organic polymer particles form the core and the hydrolyzed and condensed products of one or more hydrolyzable silicon compounds form the shell.

[0069] The core-shell particles obtained by the core-shell particle formation process may be subjected to washing, solvent replacement, filtration, drying, etc., as appropriate.

[0070] The solvent removal step is a step of removing the solvent from the core-shell particle dispersion to obtain powdered core-shell particles. In the solvent removal step, there are no particular limitations on the method of removing the solvent from the core-shell particle dispersion. Examples include heating and drying the core-shell particle dispersion at a temperature above the boiling point of the solvent to evaporate and remove the solvent, filtering the core-shell particle dispersion to perform solid-liquid separation and remove the solvent, and centrifuging the core-shell particle dispersion to perform solid-liquid separation and remove the solvent.

[0071] The calcination process is a process of obtaining hollow, porous silica particles by calcining core-shell particles, or by first thermally decomposing organic polymer particles and then calcining them. In other words, there are two forms of calcination: (i) calcining the core-shell particles without thermal decomposition treatment, and (ii) calcining the core-shell particles after thermal decomposition treatment. In thermal decomposition and calcination, the thermal decomposition temperature and calcination temperature should be selected so that the sustained release property is not lost and necking (aggregation) is unlikely to occur.

[0072] Examples of methods for producing raw porous silica particles having a core-shell structure in which such organic polymer particles form the core and porous silica form the shell include the methods described in International Publication No. 2024 / 085219 and Japanese Patent Publication No. 2020-176037.

[0073] Core-shell particles having a core made of pyrolytic organic polymer particles and a shell made of porous silica are, for example, core-shell particles obtained by performing a core-shell particle formation step and a solvent removal step according to the above-mentioned method for producing hollow raw porous silica particles. In other words, a method for producing core-shell particles having a core made of pyrolytic organic polymer particles and a shell made of porous silica is a method for producing core-shell particles that includes a core-shell particle formation step and a solvent removal step according to the above-mentioned method for producing hollow raw porous silica particles.

[0074] Since the raw porous silica particles are obtained by the sol-gel method, they have a low metal impurity content. The metal impurity content of the raw porous silica particles is 100 ppm by mass or less. If the raw porous silica particles contain multiple types of metals, the above metal impurity content refers to the total content of those multiple metals.

[0075] By selecting the manufacturing conditions for the raw porous silica particles, the type and concentration of alkoxysilane, the type and / or amount of catalyst, the water concentration, the reaction temperature, etc., the particle size, pore size distribution, pore volume, etc. of the raw porous silica particles are adjusted so that the particle size, pore size distribution, pore volume, etc. of the porous silica particles obtained by the first and second heat treatment steps are to the desired values.

[0076] If the raw material porous silica particles are solid or hollow, they may contain organic matter derived from the hydrolyzable silicon compound used as a raw material in the sol-gel process and produced as a by-product during hydrolysis and condensation reactions. Furthermore, if the raw material porous silica particles are core-shell particles having a core made of thermally decomposable organic polymer particles and a shell made of porous silica, they contain organic matter derived from the hydrolyzable silicon compound used as a raw material in the sol-gel process and produced as a by-product during hydrolysis and condensation reactions, as well as the thermally decomposable organic polymer constituting the core particles. The "organic matter derived from the hydrolyzable silicon compound used as a raw material in the sol-gel process and produced as a by-product during hydrolysis and condensation reactions" and the "thermally decomposable organic polymer constituting the core particles" contained in the raw material porous silica particles are thermally decomposed into carbon by heating in the first heat treatment step and burned away by heating in the second heat treatment step.

[0077] The pyrolytic carbon source relating to the porous silica particles of the present invention is an organic compound having at least C and H elements, preferably at least C, H and O elements, and which undergoes thermal decomposition to produce carbon in the first heat treatment step. Examples of pyrolytic carbon sources include organic carboxylic acids such as acetic acid, formic acid, propionic acid, acrylic acid, oxalic acid, tartaric acid, maleic acid, fumaric acid, adipic acid, phthalic acid, terephthalic acid, lactic acid, succinic acid, malic acid, citric acid, benzoic acid, and lauric acid; organic carboxylic acid esters such as ethyl acetate, isoamyl acetate, isobutyl acetate, phenethyl acetate, ethyl propionate, isoamyl propionate, isobutyl propionate, and fethinyl propionate; and polymer resins consisting of C, H and O such as polyethylene glycol, polyethylene oxide, polyvinyl butyral, polyvinyl alcohol, and acrylic.

[0078] The molecular weight of the pyrolytic carbon source is preferably 50 to 45,000, more preferably 150 to 1,000. Having the molecular weight of the pyrolytic carbon source within this range enhances the effect of suppressing sintering of porous silica particles during the first heat treatment step, and also reduces furnace contamination by tar components generated by pyrolysis.

[0079] In the first heat treatment step, the amount of pyrolytic carbon source mixed is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 2 parts by mass, per 100 parts by mass of raw porous silica particles. By having the amount of pyrolytic carbon source mixed within the above range, the effect of suppressing the sintering of porous silica particles with each other in the first heat treatment step is enhanced. On the other hand, if the amount of pyrolytic carbon source mixed is less than the above range, the suppression of sintering of porous silica particles with each other becomes insufficient, and if it exceeds the above range, there is a large amount of tar components due to the decomposition of organic matter in the first heat treatment step, making furnace contamination more likely.

[0080] The method for mixing the raw porous silica particles and the pyrolytic carbon source is not particularly limited. Examples include mixing the pyrolytic carbon source as a powder with the raw porous silica particles, or dissolving the pyrolytic carbon source in water or an organic solvent and then mixing the dissolved pyrolytic carbon source with the raw porous silica particles. From the viewpoint of uniformly mixing the raw porous silica particles and the pyrolytic carbon source, it is desirable to dissolve the pyrolytic carbon source in water or an organic solvent and then mix it with the raw porous silica particles using a stirring device such as a mixer. Since polar solvents such as water have better dispersibility of silica particles, from this viewpoint, it is preferable that the pyrolytic carbon source is a substance with high solubility in water.

[0081] In the first heat treatment step, a mixture of raw porous silica particles and a pyrolytic carbon source is heated under an inert gas atmosphere such as nitrogen gas, helium gas, or argon gas. The heating temperature when heating the mixture of raw porous silica particles and the pyrolytic carbon source in the first heat treatment step is 1000 to 1200°C, preferably 1050 to 1200°C, and more preferably 1100 to 1200°C. In the first heat treatment step, by heating the mixture of raw porous silica particles and the pyrolytic carbon source under an inert gas atmosphere and at the above heating temperature, carbonization occurs due to the thermal decomposition of the pyrolytic carbon source, and carbon is generated between the porous silica particles. The generated carbon suppresses the sintering of the porous silica particles when the porous silica particles are heated at high temperatures. Furthermore, by heating the mixture of raw porous silica particles and the pyrolytic carbon source at the above heating temperature in the first heat treatment step, the raw porous silica particles are heated to a high temperature, which increases the mechanical strength of the porous silica particles. Furthermore, if the raw material porous silica particles are derived from hydrolyzable silicon compounds and contain organic substances produced as by-products during hydrolysis and condensation reactions, as well as organic polymers that form the core of the core-shell particles, these organic substances and organic polymers will be thermally decomposed by heating in the first heat treatment step, generating carbon. On the other hand, if the atmosphere during heating in the first heat treatment step is an oxidizing atmosphere rather than an inert gas atmosphere, the generated carbon will burn away, and the sintering suppression effect of carbon on porous silica particles will not be obtained. Furthermore, if the heating temperature in the first heat treatment step is below the above range, the improvement in the strength of the porous silica particles will be insufficient, and the mechanical strength will not be high. If it exceeds the above range, the silica particles will melt and necking (aggregation) will occur, forming coarse particles.

[0082] In the first heat treatment step, a lower water content in the inert gas is preferable in that it can lower the partial pressure of oxygen in the furnace, and a dew point of -55°C or lower is preferable, and a dew point of -60°C or lower is more preferable.

[0083] The second heat treatment step involves heating the first heat-treated product obtained in the first heat treatment step at a temperature lower than the heating temperature in the first heat treatment step, but between 900 and 1000°C, under an oxygen-containing gas atmosphere, to obtain the second heat-treated product.

[0084] In the second heat treatment step, the first heat treatment material is heated in an oxygen-containing gas atmosphere such as oxygen gas or air. The heating temperature when heating the first heat treatment material in the second heat treatment step is lower than the heating temperature in the first heat treatment step, preferably 50°C or more lower than the heating temperature in the first heat treatment step, more preferably 100°C or more lower than the heating temperature in the first heat treatment step, and more preferably 200 to 300°C lower than the heating temperature in the first heat treatment step. For example, if the heating temperature in the first heat treatment step was 1200°C, then a temperature lower than the heating temperature in the first heat treatment step refers to a temperature less than 1200°C, a temperature 50°C or more lower than the heating temperature in the first heat treatment step refers to 1150°C or lower, a temperature 100°C or more lower than the heating temperature in the first heat treatment step refers to 1100°C or lower, and a temperature 200 to 300°C lower than the heating temperature in the first heat treatment step refers to 900 to 1000°C. The heating temperature in the second heat treatment step is lower than the heating temperature in the first heat treatment step, preferably by the aforementioned temperature, which makes it difficult for the porous silica particles to sinter with each other.

[0085] Furthermore, in the second heat treatment step, the heating temperature when heating the first heat treatment material is 900 to 1000°C, preferably 900 to 975°C, and more preferably 900 to 950°C. In the second heat treatment step, by heating the first heat treatment material at the above heating temperature under an oxygen-containing gas atmosphere, the carbon in the first heat treatment material is burned off, and the second heat treatment material is obtained. Note that the temperature at which porous silica particles sinter together varies depending on the particle size of the porous silica particles, so a heating temperature that does not cause sintering between particles is appropriately selected for each porous silica particle. Furthermore, if the raw material porous silica particles are derived from hydrolyzable silicon compounds and contain organic substances produced as by-products during hydrolysis and condensation reactions, or organic polymers that form the core of core-shell particles, the first heat-treated product will contain carbon, which is a thermal decomposition product of these substances. However, such carbon is burned away by heating in the second heat treatment step. On the other hand, if the heating temperature in the second heat treatment process is below the above range, carbon will remain in the porous silica particles, and if it exceeds the above range, the porous silica particles will sinter together.

[0086] In the second heat treatment step, the oxygen content in the oxygen-containing gas should be within a range that can burn off the carbon, preferably 1 volume percent or more.

[0087] The second heat-treated product obtained by the second heat treatment step may be obtained as the porous silica particles of the present invention, or, if necessary, it may be crushed, classified, or otherwise obtained as the porous silica particles of the present invention.

[0088] Thus, the porous silica particles of the present invention are obtained by heating a mixture of raw porous silica particles obtained by the sol-gel method and a pyrolytic carbon source at 1000 to 1200°C under an inert gas atmosphere, and then heating it at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C under an oxygen-containing atmosphere. In other words, the porous silica particles of the present invention are obtained by performing a first heat treatment step in which a mixture of raw porous silica particles and a pyrolytic carbon source is heated at 1000 to 1200°C under an inert gas atmosphere to obtain a first heat-treated product, and a second heat treatment step in which the first heat-treated product is heated at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C under an oxygen-containing gas atmosphere to obtain a second heat-treated product.

[0089] Since the required average particle size of porous silica particles differs depending on the application, the average particle size of the porous silica particles of the present invention is appropriately selected according to the application, but is preferably 10 to 1000 nm, and more preferably 80 to 500 nm. In this invention, the method for measuring the average particle size of porous silica particles involves measuring the particle size distribution of porous silica powder using a laser diffraction / scattering particle size distribution analyzer (LA-950, manufactured by Horiba, Ltd.), and calculating the average particle size as the particle size at 50% of the cumulative frequency in terms of volume (D50).

[0090] The maximum frequency of the pore size distribution of the porous silica particles of the present invention is preferably 0.1 to 20 nm, more preferably 0.5 to 10 nm. Having the maximum frequency of the pore size distribution of the porous silica particles within this range improves the packing and sustained release properties of the active ingredient.

[0091] The ratio of the total pore volume of 0 to 10 nm to the total pore volume of 0 to 100 nm in the pore size distribution of the porous silica particles of the present invention ((total pore volume of 0 to 10 nm / total pore volume of 0 to 100 nm) × 100) is preferably 1 to 10%, more preferably 2 to 8%. When the ratio of the total pore volume of 0 to 10 nm to the total pore volume of 0 to 100 nm in the pore size distribution of the porous silica particles is within the above range, the packing and sustained release properties of the active ingredient are improved.

[0092] Since the required total pore volume of porous silica particles differs depending on the application, the total pore volume of the porous silica particles of the present invention is appropriately selected according to the application, but preferably 0.1 to 5.0 cm². 3 / g, more preferably 0.5-3.0cm 3 It is / g.

[0093] In this invention, the maximum frequency of the pore size distribution of porous silica particles, the ratio of the sum of pore volumes between 0 and 10 nm to the sum of pore volumes between 0 and 100 nm in the pore size distribution, and the sum of pore volumes can be obtained by using a gas adsorption measuring device to determine the adsorption / desorption isotherm of nitrogen gas at liquid nitrogen temperature for a sample heat-treated at 300°C for 30 minutes or more under vacuum, and then analyzing the desorption side using the BJH method.

[0094] The metal impurity content of the porous silica particles of the present invention is preferably 100 ppm by mass or less, more preferably 10 ppm by mass or less. Having the metal impurity content of the porous silica particles within this range makes it difficult for the supported compound to react with the metal impurity, resulting in high sustained release ability and efficient expression of the desired effect without denaturation of the supported compound. Furthermore, having the metal impurity content of the porous silica particles within this range also reduces contamination of the filler dispersion medium, thus not hindering its function in the application. In this invention, the method for measuring the metal impurity content of porous silica particles is to use an inductively coupled plasma mass spectrometer (ICP-MS). Furthermore, if the porous silica particles contain multiple types of metals, the above-mentioned metal impurity content is the sum of the content of those multiple types of metals.

[0095] The true density of the shell portion in the solid porous silica particles and hollow porous silica of the present invention is preferably 1.2 to 2.2 g / cm³. 3 , more preferably 1.4 to 2.1 g / cm³ 3Therefore, the porous silica particles of the present invention are manufactured by the sol-gel method, and thus have a lower true density than crystalline silica. In this invention, the true density of porous silica particles can be measured using a nitrogen gas pycnometer (Ultrapyc 5000 Micro, manufactured by Anton Paar Japan Co., Ltd.).

[0096] The porous silica particles of the present invention preferably have a particle count of 10% or less, more preferably 5% or less, that is destroyed by high-pressure homogenizer treatment at 245 MPa. Having a particle count of 10% or less destroyed by high-pressure homogenizer treatment at 245 MPa within this range makes the particles less likely to break during processes such as resin mixing. In this invention, the measurement of the percentage of particles destroyed by high-pressure homogenizer treatment at 245 MPa is performed as follows. First, the sample to be measured is treated in a high-pressure homogenizer at 245 MPa for 5 passes. Next, the sample after treatment is observed using a scanning electron microscope (SEM), and particles whose spherical structure has been broken are identified as destroyed particles, and their number is counted, as well as the total number of particles. Then, the percentage of destroyed particles among the total number of particles is calculated.

[0097] The porous silica particles of the present invention, when pressurized by cold isostatic methods at an applied pressure of 190 MPa, preferably have a particle count of 10% or less, more preferably 8% or less, that is destroyed. Having the particle count of the porous silica particles destroyed by cold isostatic methods at an applied pressure of 190 MPa within this range makes the particles less likely to break during process handling, such as during resin mixing. In this invention, the method for measuring the percentage of particles that are destroyed when pressurized at a pressure of 190 MPa using the cold isostatic method is as follows: First, a predetermined amount of the sample to be measured is placed in a vacuum pack and degassed, and then pressurized at a pressure of 190 MPa in water for 1 minute using a cold isostatic press. Next, the sample after pressurization is observed using a scanning electron microscope (SEM), and particles whose spherical structure has been broken are identified as destroyed particles, and their number is counted, as well as the total number of particles. Then, the percentage of destroyed particles among the total number of particles is calculated.

[0098] The porous silica particles of the present invention, having a porous structure, are suitably used as sustained-release carriers for supporting functional ions that can provide various effects, such as fluoride ions, zinc ions, and other ions. Furthermore, despite having a porous structure, the porous silica particles of the present invention have high mechanical strength, making them less susceptible to breakage during process handling in resin compounding.

[0099] Applications of the porous silica particles of the present invention include those requiring the sustained release or recharge of supported functional compounds. For example, the porous silica particles of the present invention are suitably used as a sustained-release carrier for functional compounds such as pharmaceuticals, agrochemicals, cosmetics, detergents, or fragrances.

[0100] The present invention provides a method for producing porous silica particles, comprising a first heat treatment step in which a mixture of raw porous silica particles obtained by the sol-gel method and a pyrolytic carbon source is heated at 1000-1200°C under an inert gas atmosphere to obtain a first heat-treated product, A second heat treatment step involves heating the first heat-treated product in an oxygen-containing gas atmosphere at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C to obtain a second heat-treated product. This is a method for producing porous silica particles, characterized by having the following characteristics:

[0101] The raw material porous silica particles, pyrolytic carbon source, mixture thereof, first heat treatment product, first heat treatment step, second heat treatment product, second heat treatment step, and the resulting porous silica particles in the method for producing porous silica particles of the present invention are the same as the raw material porous silica particles, pyrolytic carbon source, mixture thereof, first heat treatment product, first heat treatment step, second heat treatment product, second heat treatment step, and the resulting porous silica particles in the silica porous method of the present invention.

[0102] Details of the porous silica particles obtained by the method for producing porous silica particles of the present invention are as described in the description of the porous silica particles of the present invention.

[0103] The present invention provides a method for producing porous silica particles. In the first heat treatment step, a mixture of raw porous silica particles obtained by the sol-gel method and a pyrolytic carbon source is heated at 1000 to 1200°C under an inert gas atmosphere. This heats the raw porous silica particles to a high temperature, increasing their mechanical strength. Simultaneously, the pyrolytic carbon source is thermally decomposed to generate carbon, creating carbon between the porous silica particles. This improves the mechanical strength of the porous silica particles without sintering them. Then, in the second heat treatment step, the first heat treatment material is heated at a temperature lower than the heating temperature in the first heat treatment step, at 900 to 1000°C, under an oxygen-containing gas atmosphere. This burns off the carbon present between the porous silica particles, resulting in porous silica particles with improved strength. Therefore, the present invention provides a method for producing porous silica particles that have a porous structure while maintaining high mechanical strength.

[0104] On the other hand, if melting of the silica occurs during heating, such as during calcination, accompanied by necking (aggregation due to sintering), the pores become filled and disappear, resulting in a decrease or complete loss of sustained release properties. [Examples]

[0105] Next, the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited in any way by the following examples.

[0106] (Example 1) <Raw material: porous silica particles> As the raw material porous silica particles, porous silica particles (manufactured by Fuso Chemical Industries, Ltd., Quartron® PL-10H) were used. The average particle size of these porous silica raw materials is 212 nm, the maximum frequency of the pore size distribution is 2.2 nm, the ratio of the total pore volume of 0-10 nm to the total pore volume of 0-100 nm is 40%, and the BET specific surface area is 30 m². 2 It was / g.

[0107] <First heat treatment process and second heat treatment process> The obtained porous silica particles were heat-treated at 1000°C for 2 hours under a dry nitrogen gas atmosphere (dew point: -60°C) to obtain the first heat-treated product. Next, the first heat-treated material was subjected to a heat treatment at 900°C for 2 hours in an air atmosphere to obtain the second heat-treated material. The second heat-treated product was obtained as the target porous silica particles. The average particle size of the obtained porous silica particles was 200 nm, the maximum frequency of the pore size distribution was 2.7 nm, and the ratio of the total pore volume of 0-10 nm to the total pore volume of 0-100 nm was 8.5%.

[0108] <Measurement of physical properties of raw porous silica particles and target porous silica particles> (Measurement of BET specific surface area) Samples that had been heat-treated at 300°C for more than 30 minutes under vacuum using an Autosorb iQ-MP manufactured by Anton Paar were measured by nitrogen gas adsorption (BET) method. (Measurement of average particle size) The particle size distribution of the sample was measured using a laser diffraction / scattering particle size distribution analyzer (LA-950, manufactured by Horiba, Ltd.), and the average particle size was calculated as the particle size at 50% of the cumulative frequency in terms of volume (D50). (Measurement of pore distribution curve) First, samples for measurement were prepared by heat treatment at 800°C for 1 hour. Then, using an Autosorb iQ-MP manufactured by Anton Paar, the samples were heat-treated at 300°C for more than 30 minutes under vacuum. The adsorption / desorption isotherms of nitrogen gas at liquid nitrogen temperature were determined, and the desorption side was analyzed using the BJH method to measure the pore size distribution curve. Next, based on the obtained pore distribution curve, the maximum frequency of the pore size distribution and the ratio of the total pore volume of 0-10 nm to the total pore volume of 0-100 nm were determined.

[0109] <Measurement of the number percentage of particles destroyed by high-pressure homogenizer treatment at 245 MPa> First, the sample was subjected to a high-pressure homogenizer treatment using a high-pressure homogenizer device, undergoing five passes at 245 MPa. Next, the treated sample was observed using a scanning electron microscope (SEM), and particles with fractured spherical structures were identified as fractured particles. The number of these fractured particles and the total number of particles were then counted. Finally, the percentage of fractured particles among the total number of particles was calculated.

[0110] <Observation of necking> Using a laser diffraction / scattering particle size distribution analyzer (LA-950, manufactured by Horiba, Ltd.), the particle size distribution of porous silica powder was measured. If a peak with a peak height of 5% or more of the main peak was observed on the larger particle size side of the most frequent main particle peak, it was determined that necking (aggregation) was present. If there were no peaks other than the main particle with a peak height of 5% or more of the main peak, it was determined that necking (aggregation) was not present.

[0111] <Sustained-release test> 1 g of the sample was placed in 8 g of a 0.6 mol / L sodium fluoride aqueous solution and allowed to stand under vacuum and under air at 1 hour intervals, repeating this procedure five times to impregnate the sample with fluoride ions. Next, the supernatant was removed by centrifugation (30,000 rpm, 5°C, 30 minutes), and an equal volume of ultrapure water was added to the supernatant. After 0, 7, and 30 days, the fluoride ion concentration in the supernatant recovered by centrifugation was analyzed again to evaluate the sustained release property. If the increase in fluoride concentration on day 7 compared to day 0 (initial immersion) was 5% or more, and the increase in concentration on day 30 compared to the fluoride concentration on day 7 was 1.5% or more, it was judged to have "sustained release property," and if these conditions were not met, it was judged to have "no sustained release property."

[0112] (Examples 2-3, Comparative Examples 1-10) The procedure was carried out in the same manner as in Example 1, except that the heating temperature and atmosphere for the first and second heat treatment steps were as shown in Tables 1 to 3. Note that Comparative Examples 1, 2, and 3 did not include the first heat treatment step.

[0113] [Table 1]

[0114] [Table 2]

[0115] [Table 3]

[0116] [Table 4] [Industrial applicability]

[0117] According to the present invention, porous silica particles having high mechanical strength can be provided as a carrier for applications where sustained release from the carrier is required.

Claims

1. Porous silica particles are characterized by being obtained by performing a first heat treatment step of heating a mixture of raw material porous silica particles obtained by the sol-gel method and a pyrolytic carbon source at 1000 to 1200°C under an inert gas atmosphere to obtain a first heat-treated product, and a second heat treatment step of heating the first heat-treated product at a temperature lower than the heating temperature of the first heat treatment step and at 900 to 1000°C under an oxygen-containing gas atmosphere to obtain a second heat-treated product.

2. The porous silica particles according to claim 1, characterized in that the percentage of particles destroyed by high-pressure homogenizer treatment at 245 MPa is 10% or less.

3. The porous silica particles according to claim 1, characterized in that the percentage of particles that are destroyed when pressurized at an applied pressure of 190 MPa by the cold isostatic method is 10% or less.

4. The porous silica particles according to claim 1, characterized in that the metal impurity content is 100 ppm by mass or less.

5. The porous silica particles according to claim 1, characterized in that the maximum frequency of the pore size distribution is 0.1 to 20 nm.

6. The porous silica particles according to claim 1, characterized in that, in the pore size distribution, the ratio of the total pore volume of 0 to 10 nm to the total pore volume of 0 to 100 nm is 1 to 10%.

7. A first heat treatment step involves heating a mixture of porous silica particles obtained by the sol-gel method and a pyrolytic carbon source at 1000-1200°C under an inert gas atmosphere to obtain a first heat-treated product. A second heat treatment step involves heating the first heat-treated product in an oxygen-containing gas atmosphere at a temperature lower than the heating temperature of the first heat treatment step and between 900 and 1000°C to obtain a second heat-treated product. A method for producing porous silica particles, characterized by having the following characteristics.

Citation Information

Patent Citations

  • Porous hollow silica particle

    JP2012051770A

  • Perfume application agent

    JP2015116334A

  • Spherical hollow silica particle composition, inclusion agent, dispersion and aqueous dispersion

    JP2022034094A